2017
DOI: 10.1002/cpt.711
|View full text |Cite
|
Sign up to set email alerts
|

Refining Liver Safety Risk Assessment: Application of Mechanistic Modeling and Serum Biomarkers to Cimaglermin Alfa (GGF2) Clinical Trials

Abstract: Cimaglermin alfa (GGF2) is a recombinant human protein growth factor in development for heart failure. Phase I trials were suspended when two cimaglermin alfa‐treated subjects experienced concomitant elevations in serum aminotransferases and total bilirubin, meeting current US Food and Drug Administration criteria for a serious liver safety signal (i.e., “Hy's Law”). We assayed mechanistic biomarkers in archived clinical trial serum samples which confirmed the hepatic origin of the aminotransferase elevations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
(21 reference statements)
2
25
1
Order By: Relevance
“…While the observed biomarker elevations were sufficient to qualify these participants as Hy's law cases and were clearly glial growth factor 2‐related, DILIsym modeling based on the serial ALT values estimated that the percentage of hepatocyte loss was well less than the 30% predicted to cause a rise in TBIL >2× ULN and this was true whether the hepatocyte death was modeled as apoptotic or necrotic. This supported the conclusion that these two participants should not be considered Hy's law cases . Subsequent studies in cultured human hepatocytes have suggested that the rise in serum bilirubin value may have resulted from the altered expression of bilirubin transporters …”
Section: Making the Most Of Traditional Biomarkers: In Silico Modelingsupporting
confidence: 55%
See 1 more Smart Citation
“…While the observed biomarker elevations were sufficient to qualify these participants as Hy's law cases and were clearly glial growth factor 2‐related, DILIsym modeling based on the serial ALT values estimated that the percentage of hepatocyte loss was well less than the 30% predicted to cause a rise in TBIL >2× ULN and this was true whether the hepatocyte death was modeled as apoptotic or necrotic. This supported the conclusion that these two participants should not be considered Hy's law cases . Subsequent studies in cultured human hepatocytes have suggested that the rise in serum bilirubin value may have resulted from the altered expression of bilirubin transporters …”
Section: Making the Most Of Traditional Biomarkers: In Silico Modelingsupporting
confidence: 55%
“…DILIsym is also being used to interpret the significance of TBIL elevations in clinical trials. A recent example is cimaglermin alfa, a recombinant version of glial growth factor 2, that caused both ALT and TBIL elevations in two participants during a phase I clinical trial, prompting a suspension of further clinical studies . While the observed biomarker elevations were sufficient to qualify these participants as Hy's law cases and were clearly glial growth factor 2‐related, DILIsym modeling based on the serial ALT values estimated that the percentage of hepatocyte loss was well less than the 30% predicted to cause a rise in TBIL >2× ULN and this was true whether the hepatocyte death was modeled as apoptotic or necrotic.…”
Section: Making the Most Of Traditional Biomarkers: In Silico Modelingmentioning
confidence: 99%
“…Furthermore, this can be adjusted as a parameter within our model to reflect the clinical situation. There are a number of clinical studies now published that have measured these biomarkers from human studies in a time‐dependent way . The approach we describe to modify dose adjustment can also be undertaken to reflect biomarker kinetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…This estimate has been used together with the AUC of serum ALT in two subjects who experienced elevations in serum ALT >3× ULN and serum TBIL >2× ULN believed as a result of study drug, ie both were Hy's Law cases by current definition. The serial serum ALT values resulted in estimates predicting the loss of hepatocytes as far <40% in each subject . The conclusion from the modelling was that the rise in serum TBIL was not due solely to hepatocellular toxicity.…”
Section: Traditional Dili Biomarkers and Hy's Lawmentioning
confidence: 99%